2019
DOI: 10.3389/fpsyg.2019.02664
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Understanding of Parental Views and Actions on Social Media Influencers Targeted at Adolescents: The Roles of Parents’ Social Media Use and Empowerment

Abstract: Recent studies suggest that adolescents are spending significant amounts of time on social media. Brands are taking advantage of this fact and actively using social media to reach adolescent consumers, primarily via social media influencers. Adolescents consider the sponsored brand posts by social media influencers to be trustworthy and honest, thus reducing their critical evaluation of the ads. While several researchers have pointed to the critical role that parents play in their adolescents becoming digitall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 53 publications
1
50
0
1
Order By: Relevance
“…One particular shortcoming of recent marketing literacy studies is that they have primarily investigated the influence of school-based interventions and, to a lesser extent, parental explanations about marketing. However, research has shown that parental mediation can increase children's knowledge and understanding of marketing because parents more than educators can intervene on marketing exposure with higher frequency and higher contextspecify (De Pauw et al, 2019;Hudders & Cauberghe, 2018;Lin et al, 2019;Nelson et al, 2017;Pearce & Baran, 2018). Consequently, interventions targeting the improvement of parental mediation for marketing could be a highly valuable area of research.…”
Section: Marketing Literacy As Dependent Variable In Intervention Stumentioning
confidence: 99%
See 4 more Smart Citations
“…One particular shortcoming of recent marketing literacy studies is that they have primarily investigated the influence of school-based interventions and, to a lesser extent, parental explanations about marketing. However, research has shown that parental mediation can increase children's knowledge and understanding of marketing because parents more than educators can intervene on marketing exposure with higher frequency and higher contextspecify (De Pauw et al, 2019;Hudders & Cauberghe, 2018;Lin et al, 2019;Nelson et al, 2017;Pearce & Baran, 2018). Consequently, interventions targeting the improvement of parental mediation for marketing could be a highly valuable area of research.…”
Section: Marketing Literacy As Dependent Variable In Intervention Stumentioning
confidence: 99%
“…Most research of parental mediation in the context of marketing and advertising was conducted for traditional ads, such as television (Bijmolt et al, 1998;Buijzen & Mens, 2007;Buijzen & Valkenburg, 2003b;Robertson, 1979;Vijayalakshmi et al, 2019), and movies (Hudders & Cauberghe, 2018;Hudson et al, 2008;Naderer et al, 2018). More recently, studies on parental mediation in new marketing and advertising formats are slowly emerging, such as for advergames (Evans, 2014;Evans et al, 2013;Evans & Hoy, 2016), social network games , online advertising (Cornish, 2014;Kowalczyk & Royne, 2016;Vijayalakshmi et al, 2018) and influencer marketing (Evans et al, 2018;Lin et al, 2019;Lou & Kim, 2019). Most parental marketing mediation studies focus on mediation as the explanatory and explained variable, while less focus on it as the outcome variable.…”
Section: Parental Mediation Of Marketing and Advertisingmentioning
confidence: 99%
See 3 more Smart Citations